STATE REGULATION OF ANTI-CORRUPTION ACTIVITIES IN UKRAINE DURING MARTIAL LAW - Vitalii Kotsur; Oleksiy S. Hovpun; Serhii Podhorets; Anastasiia Metil; Tetiana Chasova (Journal of International Legal Communication, 2024)
Since the 1950s, corruption has been an important topic of academic investigation and continues to be relevant nowadays. Scholars, international organizations, ordinary citizens and other beneficiaries continue to pay attention to this issue, as well as to the social projects, political economics, and social implications of corruption's expansion, economic resource allocation, the national regulator, and others. This analysis is particularly important in light of the current Russian-Ukrainian war, which has far-reaching implications, undermining national development, reducing public confidence and posing new threats to national security. Consequently, in developing effective strategies to repel the aggression of the Russian Federation, tackling corruption appears as an essential part of the multifaceted challenges. Therefore, the primary objective of this study is to elucidate the complexities of the country’s legal frameworks related to anti-corruption efforts in Ukraine in the post-war context and to provide recommendations on effective anti-corruption policies. For this purpose, the following methods were used: social statistical analysis, survey analysis, system-structure analysis, classification and categorizing operations, deductive reasoning, abstraction, dialectical inquiry, modelling, synthesis and analysis of relevant data